Prevalence of Yersinia Species in the Ileum of Crohn's Disease Patients and Controls - Guillaume Le Baut; Guillaume Le Baut; Claire O'Brien; Claire O'Brien; Paul Pavli; Paul Pavli; Maryline Roy; Philippe Seksik; Xavier Tréton; Xavier Tréton; Stéphane Nancey; Stéphane Nancey; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Yersinia are common contaminants of food products, but their prevalence in the human gut is poorly documented. Yersinia have been implicated in Crohn's Disease (CD, an inflammatory bowel disease) however their role in CD is controversial. We performed highly sensitive PCR assays of specific sequences for the gyrB gene of Y. aldovae, Y. bercovieri, Y. enterocolitica, Y. intermedia, Y. mollaretii and the inv gene of Y. pseudotuberculosis. We analyzed a total of 470 ileal samples taken from 338 participants (262 CD patients and 76 controls) belonging to three independent cohorts. All patients and controls were phenotyped and genotyped for the main CD susceptibility variants: NOD2, ATG16L1, and IRGM. Yersinia were found in 7.7% of ileal samples (respectively 7.9 and 7.6% in controls and CD patients) corresponding to 10% of participants (respectively 11.8 and 9.5% in controls and CD patients). Y. enterocolitica, Y. pseudotuberculosis and Y. intermedia were the most frequently identified species. The bacteria were more frequent in resected specimens, lymph nodes and Peyer's patches. Yersinia were no more likely to be detected in CD tissues than tissues from inflammatory and non-inflammatory controls. CD patients treated with immunosuppressants were less likely to be Yersinia carriers. In conclusion, this work shows that Yersinia species are frequently found at low levels in the human ileum in health and disease. The role of Yersinia species in this ecosystem should now be explored.